STATUS HARA N, P DAN K PADA TANAH SAWAH IRIGASI DI KAPANEWON PRAMBANAN, KABUPATEN SLEMAN, DAERAH ISTIMEWA YOGYAKARTA - Wibawati, Widya; Mulyanto, Djoko; Munawar, Ali (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
The difference in the productivity level of paddy is caused by nutrient availability and land management. This study aims to determine the chemical properties of soil, especially elements of N, P, and K, in soils that have different levels of rice productivity. The methods used in this study are survey methods and laboratory analysis. Purposive sampling was conducted based on the productivity of medium and high-status rice fields. Based on the level of productivity of rice fields, there are 18 sample points, which are composite into 7 samples and analyzed in the laboratory. The results showed that several chemical properties in areas with high productivity levels had an average availability of total N nutrient status of 0.17% (low), potential P 56.5 mg 100 g-1 (high), potential K 17 mg 100 g-1 (low), organic C by 2.75% (medium), cation exchange capacity (CEC) 11.52 cmol(+)kg-1 (low) while in areas with medium productivity had an average total N nutrient of 0.23% (medium), potential P 38.33 mg 100 g-1 (medium), potential K 72 mg 100 g-1 (very high), organic C 3.23% (high), CEC 33.06 cmol(+)kg-1 (high) and has a soil pH of 6.1 (slightly acid) respectively. High-productivity areas have low to medium soil fertility, while medium-productivity areas have medium to high soil fertility. Rice field management factors are suspected to cause differences in rice productivity levels.